Ambulatory Sedation in Pediatric Dentistry “Knowledge and Practice of Dental Graduates of Karachi” A Cross Sectional Study: Ambulatory Sedation in Pediatric Dentistry - Ali, Iqra; Maryam, .; Khero, Rabail; Zareef, Uzma; Faizan, Afshan; Ahmed, Tauseef; Haque, Arifa (Pakistan Journal of Health Sciences, 2024)
Ambulatory sedation in pediatric dentistry is crucial for managing anxiety and pain, ensuring effective treatment. Assessing the knowledge and practice of dental graduates regarding this technique is essential for improving pediatric dental care. Objective: To evaluate the knowledge and practice of dental graduates in Karachi regarding ambulatory sedation in pediatric dentistry. Methods: A cross-sectional survey was conducted from July 2023 to December 2023 among dental graduates in Karachi using a simple random sampling technique. Data were collected through a structured, self-administered questionnaire, which included 5 demographic questions, 14 knowledge questions, and 3 practice questions. The knowledge questions were scored, with each correct answer allocated 1 point, and the total score categorized into poor (0-4), good (5-9), and excellent (10-14) knowledge levels. Data were analyzed using SPSS version 25.0, with descriptive statistics and Chi-square tests employed for analysis. Results: Out of 200 respondents, 45% demonstrated excellent knowledge, 40% had good knowledge, and 15% had poor knowledge regarding ambulatory sedation in pediatric dentistry. The practice assessment revealed that 60% of the graduates regularly used ambulatory sedation techniques, while 40% reported occasional use. Significant associations were found between knowledge levels and years of practice (p<0.05). Conclusions: The study indicates that while a substantial proportion of dental graduates in Karachi have excellent knowledge of ambulatory sedation, there is a need for continued education and training to ensure consistent practice. Enhancing knowledge and practice through targeted programs can improve pediatric dental care outcomes